Step-by-step explanation:
Sorryyyyy
it is not mathematics
F(x) = 4x + 7
g(x) = 3x²
(f · g)(x) = 3x²(4x + 7)
(f · g)(x) = 3x²(4x) + 3x²(7)
(f · g)(x) = 12x³ + 21x²
You want to solve this set of linear equations by the elimination method.
Let x=price of bag of flour and y=price of bag of sugar
Multiply the first equation by -3.
-3(7x+5y=584)
Multiply the second equation by 5.
5(5x+3y=384)
Solve by elimination.
X=42
Substitute value of x into one of the original equations.
Y=58
Answer:
4 radical 5
Step-by-step explanation:
Answer:
B. Gaining
Step-by-step explanation: